STRESS AND ITS IMPACT ON PHYSICAL AND MENTAL HEALTH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article examines the impact of stress on physical and mental health. Stress is a physical and psychological response of the human body that can lead to many problems. The article analyzes the impact of stress on the cardiovascular system, immune system and nervous system, as well as the fact that chronic stress causes mental conditions such as depression, anxiety and insomnia. Based on research, statistical analysis, and clinical studies, stress management methods (psychotherapy, meditation, pharmacotherapy) and their effectiveness in reducing their negative effects are discussed. The article suggests new approaches and effective treatments for stress management.